Prediction of Breast Cancer Using Big Data Analytics - Shailaja, K.; Seetharamulu, B.; A. Jabbar, M. (International Journal of Engineering and Technology, 2018)
Big data is a phrase which is used to report collection of data that vast in size and still growing exponentially with time. It covers structured unstructured and semi-structured data. Now a dayâ€™s big data is widely used in healthcare for prediction of diseases. Breast cancer is one of top cancer that occurs in a woman. It is the second main leading reason for the death of a woman in the United States and in Asian countries. If we identify this disease in early stages there is a better chance for curing. For this experiment, we used K nearest neighbor (KNN) algorithm for finding classification accuracy and it is implemented on R tool. We consider Wisconsin breast cancer (original) dataset taken from UCI machine learning repository.Â Â